Optical laminate, image display panel, and image display device
By using an optical laminate structure of an adhesive sheet with low surface resistivity and an antistatic layer under a low temperature environment in an image display device, the poor display problem caused by static electricity in a low temperature environment is solved, and the reliability of the device is improved.
Patent Information
- Application Number
- CN202480004187.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-03-16
- Filing Date
- 2024-03-13
- Publication Date
- 2025-04-25
AI Technical Summary
In low temperature environments, image display devices are prone to poor display due to static electricity, and the prior art has not yet effectively solved this problem.
The adhesive sheet formed by an adhesive composition containing a polymer and an antistatic agent is ensured that its surface resistivity at -15°C is 1.0×1010Ω/□ or less, and an antistatic layer is introduced into the optical laminate to suppress the static charge, specifically including a laminate structure using an antistatic layer and an optical film.
It effectively suppresses the electrostatic charge of the image display device in a low-temperature environment, reduces display defects, and improves the reliability of the device under low-temperature conditions.
Smart Images

Figure CN119895295A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an optical laminate, an image display panel and an image display device. Background Art
[0002] In recent years, image display devices represented by liquid crystal display devices and electroluminescent (EL) display devices (e.g., organic EL display devices, inorganic EL display devices) are rapidly becoming popular. The above-mentioned various image display devices, for example, have a stacked structure of an image display unit such as a liquid crystal unit and an EL light-emitting element, and an optical laminate including a polarizer and an adhesive sheet. The adhesive sheet is mainly used for bonding between films contained in the optical laminate, and bonding between the image display unit and the optical laminate.
[0003] Static electricity is generated when the image display device is manufactured (e.g., when the optical laminate is attached to the image display unit via an adhesive sheet) or when it is used (e.g., when the user touches the image display device). If the image display device is charged by the static electricity, problems such as poor display may occur.
[0004] Patent Documents 1 and 2 disclose a laminated structure including a polarizing film and a conductive layer containing a conductive polymer.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2016-39132
[0008] Patent Document 2: Japanese Patent Application No. 2015-509615 Summary of the invention
[0009] Problems to be solved by the invention
[0010] According to the research of the present inventors, there is still room for improvement in optical layered bodies from the viewpoint of sufficiently preventing display failures in image display devices. Therefore, an object of the present invention is to provide an optical layered body that is more suitable for suppressing display failures.
[0011] Solutions to the problem
[0012] The present inventors have found that display failure of an image display device is likely to occur in a low-temperature environment, and based on this finding, have completed the present invention.
[0013] The present invention provides an optical laminate comprising a pressure-sensitive adhesive sheet, an antistatic layer and an optical film.
[0014] The adhesive sheet is formed from an adhesive composition comprising a polymer (A) and an antistatic agent.
[0015] The surface resistivity of the adhesive sheet side of the optical laminate at -15°C was 1.0×10 10 Ω / □ or less.
[0016] Furthermore, the present invention provides an image display panel including the above-mentioned optical layered body.
[0017] Furthermore, the present invention provides an image display device including the above-mentioned image display panel.
[0018] Effects of the Invention
[0019] According to the present invention, it is possible to provide an optical layered body that is more suitable for suppressing display failure in a low-temperature environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a cross-sectional view schematically showing an example of the optical layered body according to the present embodiment.
[0021] Figure 2 This is a cross-sectional view schematically showing another example of the optical layered body according to the present embodiment.
[0022] Figure 3 This is a cross-sectional view schematically showing an example of the image display panel according to this embodiment.
[0023] Figure 4 This is a cross-sectional view schematically showing another example of the image display panel according to this embodiment.
[0024] Figure 5 This is a cross-sectional view schematically showing another example of the image display panel according to this embodiment. DETAILED DESCRIPTION
[0025] The optical layered body according to the first aspect of the present invention comprises a pressure-sensitive adhesive sheet, an antistatic layer, and an optical film.
[0026] The adhesive sheet is formed from an adhesive composition comprising a polymer (A) and an antistatic agent.
[0027] The surface resistivity of the adhesive sheet side of the optical laminate at -15°C was 1.0×10 10 Ω / □ or less.
[0028] In the second aspect of the present invention, for example, in the optical layered body of the first aspect, the surface resistivity of the antistatic layer at 25° C. is 3.0×10 8 Ω / □ or less.
[0029] In the third aspect of the present invention, for example, in the optical layered body of the first or second aspect, the surface resistivity of the antistatic layer at 25° C. is 1.0×10 7Ω / □ or more and 1.0×10 8 Ω / □ or less.
[0030] In a fourth aspect of the present invention, for example, in the optical layered body according to any one of the first to third aspects, the polymer (A) is a (meth)acrylic polymer.
[0031] In a fifth aspect of the present invention, for example, in the optical layered body according to any one of the first to fourth aspects, the polymer (A) has a polyether structure.
[0032] In a sixth aspect of the present invention, for example, in the optical layered body according to any one of the first to fifth aspects, the polymer (A) has a structural unit derived from a monomer represented by the following formula (1).
[0033] [Chemical formula 1]
[0034]
[0035] In the above formula (1), R 1 is a hydrogen atom or a methyl group, R 2 is a linear or branched alkyl group, and n is an integer of 1 to 15.
[0036] In a seventh aspect of the present invention, for example, in the optical layered body according to any one of the first to sixth aspects, the polymer (A) has a structural unit derived from an aromatic ring-containing monomer.
[0037] In an eighth aspect of the present invention, for example, in the optical layered body according to any one of the first to seventh aspects, the amount of the antistatic agent blended in the pressure-sensitive adhesive composition is less than 10 parts by weight based on 100 parts by weight of the polymer (A).
[0038] In a ninth aspect of the present invention, for example, in the optical layered body according to any one of the first to eighth aspects, the glass transition temperature of the polymer (A) calculated by the FOX equation is -40°C or lower.
[0039] In a tenth aspect of the present invention, for example, in the optical layered body according to the ninth aspect, the glass transition temperature is -45°C or lower.
[0040] An image display panel according to an eleventh aspect of the present invention includes the optical layered body according to any one of the first to tenth aspects.
[0041] An image display device according to a twelfth aspect of the present invention includes the image display panel according to the eleventh aspect.
[0042] Hereinafter, the present invention will be described in detail, but the present invention is not limited to the following embodiments and can be implemented in any modified manner without departing from the gist of the present invention.
[0043] The optical laminate of the present embodiment comprises a pressure-sensitive adhesive sheet, an antistatic layer, and an optical film. The pressure-sensitive adhesive sheet is formed from a pressure-sensitive adhesive composition containing a polymer (A) and an antistatic agent. The surface resistivity of the pressure-sensitive adhesive sheet side of the optical laminate at -15°C is 1.0×10 10 Ω / □ or less.
[0044] [Optical laminate]
[0045] Figure 1 1 is a cross-sectional view schematically showing an example of an optical laminate of the present embodiment. The optical laminate 10A includes an adhesive sheet 1, an antistatic layer 2, and an optical film 3. The optical laminate 10A has, for example, a structure in which the adhesive sheet 1, the antistatic layer 2, and the optical film 3 are sequentially laminated. The optical laminate 10A can be bonded to an object (e.g., an image display panel) via the adhesive sheet 1.
[0046] The adhesive sheet 1 is formed on the antistatic layer 2. The adhesive sheet 1 and the antistatic layer 2 are stacked on each other. The adhesive sheet 1 and the antistatic layer 2 are formed in contact with each other. The adhesive sheet 1 is formed on one main surface of the antistatic layer 2. Figure 1 In the embodiment, the adhesive sheet 1 is formed on the entire main surface of the antistatic layer 2. However, the adhesive sheet 1 may be formed only on a part of the main surface of the antistatic layer 2. In this specification, the "main surface" refers to the surface having the largest area of a film or layer.
[0047] The antistatic layer 2 is formed on the optical film 3. The antistatic layer 2 and the optical film 3 are stacked on each other. The antistatic layer 2 and the optical film 3 are formed in contact with each other. The antistatic layer 2 is formed on one main surface of the optical film 3. In detail, the optical film 3 is formed on the main surface of the antistatic layer 2 where the adhesive sheet 1 is not formed. Figure 1 In the embodiment, the optical film 3 is formed on the entire one main surface of the antistatic layer 2. However, the optical film 3 may be formed only on a part of the one main surface of the antistatic layer 2.
[0048] [Adhesive sheet]
[0049] The surface resistivity R of the adhesive sheet 1 side of the optical laminate 10A at -15°C was 1.0×10 10 Ω / □ or less. By making the optical laminate 10A have a 1.0×10 10 The pressure-sensitive adhesive sheet 1 having a surface resistivity R of Ω / □ or less can suppress display defects caused by charging of an image display device even in a low-temperature environment.
[0050] The surface resistivity R can be 5.0×10 9Ω / □ or less, 4.0×10 9 Ω / □ or less, 3.0×10 9 Ω / □ or less, 2.0×10 9 Ω / □ or less, 1.0×10 9 Ω / □ or less, 5.0×10 8 Ω / □ or less, 1.0×10 8 Ω / □ or less, 8.0×10 7 Ω / □ or less, and can be further 6.0×10 7 Ω / □ or less. The lower limit of the surface resistivity R is, for example, 1.0×10 6 Ω / □, or 1.0×10 7 Ω / □. However, when the optical laminate 10A is used for an image display panel with a built-in touch sensor function, the surface resistivity R is preferably 5.0×10 6 Ω / □ or more, more preferably 1.0×10 7 The surface resistivity R can be measured, for example, using a high resistance resistivity meter (for example, Hiresta series manufactured by MITSUBISHI CHEMICAL ANALYTECH) under the conditions of applying a voltage of 250 V for 10 seconds.
[0051] When the optical layered body 10A is subjected to a weather resistance test, the surface resistivity R′ of the pressure-sensitive adhesive sheet 1 side of the optical layered body 10A at −15° C. is, for example, 1.5×10 10 Ω / □ or less, can be 1.2×10 10 Ω / □ or less, 1.0×10 10 Ω / □ or less, 9.0×10 9 Ω / □ or less, 8.0×10 9 Ω / □ or less, 7.0×10 9 Ω / □ or less, 6.0×10 9 Ω / □ or less, 5.0×10 9 Ω / □ or less, 1.0×10 9 Ω / □ or less, 5.0×10 8 Ω / □ or less, 1.0×10 8 Ω / □ or less, 8.0×10 7 Ω / □ or less, and can be further 6.0×10 7 Ω / □ or less. The lower limit of the surface resistivity R' is, for example, 1.0×10 6 Ω / □, which can be 1.0×10 7 Ω / □. The surface resistivity R' is 5.0×10 8 Ω / □ or less, and further 1.0×108 When Ω / □ or less, display defects can be further suppressed.
[0052] The weather resistance test can be carried out by placing the product under a temperature of 40°C and a humidity of 20%RH with an illumination of 500W / m 2 The optical layered body 10A is subjected to continuous irradiation with light having a wavelength of 300 to 700 nm for 500 hours from the optical film 3 side. The weather resistance test can be performed using, for example, an ultraviolet fading meter (for example, U48HB manufactured by Suga Test Instruments Co., Ltd.).
[0053] The surface resistivity R' of the adhesive sheet 1 side of the optical laminate 10A at -15°C is not easy to change before and after the weathering test, for example. The ratio R' / R of the surface resistivity R' (Ω / □) of the adhesive sheet 1 side of the optical laminate 10A at -15°C after the weathering test to the surface resistivity R (Ω / □) of the adhesive sheet 1 side of the optical laminate 10A before the weathering test at -15°C is, for example, 7.0 or less, and can be 6.0 or less, 5.0 or less, 2.5 or less, 2.0 or less, 1.5 or less, 1.4 or less, 1.3 or less, and further can be 1.2 or less. The lower limit of the ratio R' / R is, for example, 0.25, 0.5, and further can be 0.75. When the ratio R' / R is 1.5 or less, poor display can be further suppressed.
[0054] Before the weather resistance test, the surface resistivity R1 of the pressure-sensitive adhesive sheet 1 side of the optical laminate 10A at 25° C. is, for example, 1.0×10 10 Ω / □ or less. The surface resistivity R1 is, for example, 1.0×10 9 Ω / □ or less, can be 8.0×10 8 Ω / □ or less, 5.0×10 8 Ω / □ or less, 3.0×10 8 Ω / □ or less, 2.0×10 8 Ω / □ or less, 1.0×10 8 Ω / □ or less, 8.0×10 7 Ω / □ or less, 5.0×10 7 Ω / □ or less, and can be further 2.0×10 7 Ω / □ or less. The lower limit of the surface resistivity R1 is, for example, 1.0×10 6 Ω / □, which can be 1.0×10 7 Ω / □.
[0055] The surface resistivity of the optical laminate 10A on the adhesive sheet 1 side is not easy to increase even in a low temperature environment, for example. Before the weather resistance test, the ratio R / R1 of the surface resistivity R (Ω / □) of the adhesive sheet 1 side of the optical laminate 10A at -15°C to the surface resistivity R1 (Ω / □) of the adhesive sheet 1 side of the optical laminate 10A at 25°C is, for example, 50.0 or less, and can be 40.0 or less, 30.0 or less, 20.0 or less, 15.0 or less, 10.0 or less, 8.0 or less, 7.0 or less, and further can be 5.0 or less. The lower limit of the ratio R / R1 is, for example, 0.1, 0.5, and further 1.0. When the ratio R / R1 is 50.0 or less, poor display can be further suppressed.
[0056] The ratio R' / R1 of the surface resistivity R' (Ω / □) of the adhesive sheet 1 side of the optical laminate 10A at -15°C after the weather test to the surface resistivity R1 (Ω / □) of the adhesive sheet 1 side of the optical laminate 10A before the weather test at 25°C is, for example, 60.0 or less, 55.0 or less, 50.0 or less, 45.0 or less, 40.0 or less, 35.0 or less, 30.0 or less, 25.0 or less, 20.0 or less, 15.0 or less, 10.0 or less, and further 5.0 or less. The lower limit of the ratio R' / R1 is, for example, 0.25, 0.5, 0.75, and further 1.0. When the ratio R' / R1 is 25.0 or less, 10.0 or less, and further 5.0 or less, display defects can be further suppressed.
[0057] The pressure-sensitive adhesive sheet 1 is formed from a pressure-sensitive adhesive composition (I) containing a polymer (A) and an antistatic agent.
[0058] <Polymer (A)>
[0059] Examples of polymer (A) are (meth) acrylic polymers, carbamate polymers, silicone polymers and rubber polymers. Polymer (A) may have a polyether structure. Polymer (A) is preferably a (meth) acrylic polymer. In other words, the adhesive composition (I) may contain a (meth) acrylic polymer as a main component. In other words, the adhesive composition (I) may be an acrylic adhesive composition. The main component refers to the component with the largest content rate on a weight basis in the composition. The content rate of the main component is, for example, 50% by weight or more, and may be 60% by weight or more, 70% by weight or more, 75% by weight or more, and may further be 80% by weight or more. In this specification, "(meth) acrylic polymer" refers to a polymer having a structural unit derived from a (meth) acrylic monomer such as a (meth) acrylate. The content of the structural unit derived from the (meth)acrylic monomer in the (meth)acrylic polymer is, for example, 40% by weight or more, 50% by weight or more, 60% by weight or more, 70% by weight or more, 80% by weight or more, 85% by weight or more, 90% by weight or more, and further 95% by weight or more. The (meth)acrylic polymer may contain only the structural unit derived from the (meth)acrylic monomer. "(Meth)acrylic acid" refers to acrylic acid and methacrylic acid. "(Meth)acrylate" refers to acrylate and methacrylate.
[0060] Polymer (A) may have a polyether structure. A polyether structure is a structure containing at least two ether groups (-O-). A polyether structure may be linear or branched. An example of a polyether structure includes an alkyl group which may be linear or branched, and at least two ether groups. Polymer (A) may have a polyether structure in the main chain or in the side chain, preferably in the side chain. Polymer (A) may be a (meth) acrylic polymer having a polyether structure in the side chain.
[0061] The polymer (A) may have a structural unit having a polyether structure. In the structural unit, the polyether structure may be located in the main chain or in the side chain, preferably in the side chain. The polymer (A) may have a structural unit derived from a (meth)acrylic monomer having a polyether structure in the side chain.
[0062] The polymer (A) having a polyether structure in a side chain has, for example, a structural unit derived from a monomer (A1) represented by the following formula (1). 1 is a hydrogen atom or a methyl group. 2 The alkyl group may be a linear or branched alkyl group, preferably a linear alkyl group. The number of carbon atoms in the alkyl group may be 1 to 10, and may further be 1 to 4. 2Examples of are methyl and ethyl. n is an integer of 1 to 15, preferably an integer of 1 to 10, and more preferably an integer of 1 to 5. When n is 1, the monomer (A1) contains "-O-" of the COO group and contains two ether groups. The monomer (A1) is a (meth)acrylic acid monomer, more specifically, a (meth)acrylate monomer. If we focus on R at the end of the side chain 2 O group, and the monomer (A1) is also a kind of alkoxy group-containing (meth)acrylate monomer. The structural unit derived from the monomer (A1) has a polyether structure in the side chain.
[0063] [Chemical formula 2]
[0064]
[0065] Examples of monomer (A1) are 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 2-(2-ethoxyethoxy)ethyl (meth)acrylate, methoxytriethylene glycol (meth)acrylate, and methoxypolyethylene glycol (meth)acrylate, preferably 2-methoxyethyl acrylate (MEA). The structural unit derived from monomer (A1) is particularly helpful in reducing the surface resistivity of the adhesive sheet formed by the adhesive composition (I).
[0066] The polymer (A) may have both a structural unit derived from the monomer (A1) and a structural unit derived from the monomer (A2) described below. The polymer (A) having two structural units can contribute to improving the durability of the adhesive force of the pressure-sensitive adhesive sheet 1 .
[0067] The content of the structural unit having a polyether structure in the polymer (A) (for example, a structural unit derived from the monomer (A1)) is, for example, 0% by weight or more, and can be 10% by weight or more, 15% by weight or more, 20% by weight or more, 25% by weight or more, 30% by weight or more, 35% by weight or more, 40% by weight or more, 45% by weight or more, and further can be 50% by weight or more. The upper limit of the content is, for example, 100% by weight or less, and can be 90% by weight or less, 80% by weight or less, 70% by weight or less, 65% by weight or less, 60% by weight or less, and further can be less than 60% by weight.
[0068] The polymer (A) may have one or two or more structural units derived from the following monomer (A2). The monomer (A2) shown below can be copolymerized with the monomer (A1).
[0069] An example of the monomer (A2) is a (meth)acrylic monomer having an alkyl group having 1 to 30 carbon atoms in a side chain. The alkyl group may be linear or branched. Examples of the (meth)acrylic monomer having an alkyl group in the side chain are methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, isobutyl (meth)acrylate, n-pentyl (meth)acrylate, isopentyl (meth)acrylate, n-hexyl (meth)acrylate, isohexyl (meth)acrylate, isoheptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, n-nonyl (meth)acrylate, isononyl (meth)acrylate, n-decyl (meth)acrylate, isodecyl (meth)acrylate, n-dodecyl (meth)acrylate (lauryl (meth)acrylate), n-tridecyl (meth)acrylate, n-tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, and octadecyl (meth)acrylate. The content of the structural unit derived from the (meth)acrylic monomer having an alkyl group in the side chain in the polymer (A) is, for example, 80% by weight or less, 70% by weight or less, 60% by weight or less, 50% by weight or less, 40% by weight or less, 30% by weight or less, 20% by weight or less, or 10% by weight or less, further 5% by weight or less, or 0% by weight (the structural unit may not be present).
[0070] Other examples of monomer (A2) are hydroxyl-containing monomers. Hydroxyl-containing monomers can be hydroxyl-containing (meth) acrylic acid monomers. Examples of hydroxyl-containing monomers are (meth) 2-hydroxyethyl acrylate, (meth) 3-hydroxypropyl acrylate, (meth) 4-hydroxybutyl acrylate, (meth) 6-hydroxyhexyl acrylate, (meth) 8-hydroxyoctyl acrylate, (meth) 10-hydroxydecyl acrylate and (meth) 12-hydroxylauryl acrylate (meth) acrylate and (meth) methyl acrylate (4-hydroxymethylcyclohexyl). From the viewpoint of improving the durability of the adhesive sheet formed by the adhesive composition (I), preferably (meth) 2-hydroxyethyl acrylate, (meth) 4-hydroxybutyl acrylate, more preferably (meth) 4-hydroxybutyl acrylate. The content of the structural unit derived from the hydroxyl-containing monomer in the polymer (A) is, for example, 1 to 5% by weight, can be 3% by weight or less, and can further be 2% by weight or less. Polymer (A) may also not have a structural unit derived from a hydroxyl-containing monomer.
[0071] The monomer (A2) may be an aromatic ring-containing monomer, a carboxyl group-containing monomer, an amino group-containing monomer, or an amide group-containing monomer.
[0072] The aromatic ring-containing monomer can be an aromatic ring-containing (meth) acrylic monomer. Examples of aromatic ring-containing monomers are phenyl (meth) acrylate, benzyl (meth) acrylate, phenoxydiethylene glycol (meth) acrylate, ethylene oxide-modified nonylphenol (meth) acrylate, hydroxyethylated β-naphthol (meth) acrylate and biphenyl (meth) acrylate. During the manufacture and / or use of an image display device comprising an optical laminate 10A, the adhesive sheet may be birefringent due to the offset of the adhesive sheet. Thus, problems such as light leakage and uneven display may occur in the image display device. By making the polymer (A) have a structural unit derived from an aromatic ring-containing monomer, the birefringence caused by the offset of the adhesive sheet can be reduced. Thus, the light leakage and uneven display of the image display device can be further reduced.
[0073] The aromatic ring-containing monomer may be a structural unit derived from a monomer (A3) represented by the following formula (2). 3 is a hydrogen atom or a methyl group. 4 The phenyl group is an optionally substituted hydrogen atom, preferably a phenyl group. The substituent of the hydrogen atom is, for example, a linear or branched alkyl group having 1 to 10 carbon atoms, and further 1 to 4 carbon atoms, and an alkoxy group having 1 to 4 carbon atoms. n is an integer of 1 to 15, preferably an integer of 1 to 10, and more preferably an integer of 1 to 5. When n is 1, the monomer (A3) contains the "-O-" of the COO group and contains two ether groups. The monomer (A3) is a (meth) acrylic acid monomer, and more specifically, a (meth) acrylate monomer. If we focus on R at the end of the side chain 4 O group, the monomer (A3) is also a kind of alkoxy group-containing (meth)acrylate monomer. The structural unit derived from the monomer (A3) has a polyether structure in the side chain.
[0074] [Chemical formula 3]
[0075]
[0076] An example of monomer (A3) is phenoxyethyl (meth)acrylate.
[0077] By making the polymer (A) have a structural unit derived from the monomer (A3), the durability of the optical laminate 10A can be further improved. In addition, by making the polymer (A) have a structural unit derived from the monomer (A3), there is a tendency that even if the optical film 3 in the optical laminate 10A shrinks due to heating, it is not easy to cause deviation at the end. Therefore, the optical laminate 10A using the adhesive sheet 1 is not easy to cause poor appearance such as light leakage caused by shrinkage of the optical film 3 even in a high temperature environment.
[0078] Examples of carboxyl-containing monomers are (meth)acrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, and crotonic acid. Examples of amino-containing monomers are N,N-dimethylaminoethyl (meth)acrylate and N,N-dimethylaminopropyl (meth)acrylate. Examples of amide group-containing monomers include acrylamide monomers such as (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N-isopropylacrylamide, N-methyl(meth)acrylamide, N-butyl(meth)acrylamide, N-hexyl(meth)acrylamide, N-hydroxymethyl(meth)acrylamide, N-hydroxymethyl-N-propyl(meth)acrylamide, aminomethyl(meth)acrylamide, aminoethyl(meth)acrylamide, mercaptomethyl(meth)acrylamide and mercaptoethyl(meth)acrylamide; N-acryloyl heterocyclic monomers such as N-(meth)acryloylmorpholine, N-(meth)acryloylpiperidine and N-(meth)acryloylpyrrolidine; and N-vinyl-containing lactam monomers such as N-vinylpyrrolidone and N-vinyl-ε-caprolactam.
[0079] Monomer (A2) may be a multifunctional monomer. Examples of the multifunctional monomer include hexanediol di(meth)acrylate (1,6-hexanediol di(meth)acrylate), butanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, tetramethylolmethane tri(meth)acrylate, allyl (meth)acrylate, vinyl (meth)acrylate, epoxy acrylate, polyester acrylate, and urethane acrylate; and divinylbenzene. The multifunctional acrylate is preferably 1,6-hexanediol diacrylate and dipentaerythritol hexa(meth)acrylate.
[0080] The total content of the structural units derived from aromatic ring-containing monomers, carboxyl-containing monomers, amino-containing monomers, amide-containing monomers and polyfunctional monomers in the polymer (A) is preferably 20% by weight or less, more preferably 15% by weight or less, further preferably 10% by weight or less, and particularly preferably 8% by weight or less. In the case where the polymer (A) has the structural unit, the total content is, for example, 0.01% by weight or more, 1% by weight or more, 2% by weight or more, and further 3% by weight or more. The polymer (A) may not have these structural units. In particular, in the polymer (A), the content of the structural units derived from the carboxyl-containing monomers may be less than 0.1% by weight, or 0% by weight (or may not have the structural unit).
[0081] Examples of other monomers (A2) are nitrile-containing (meth)acrylates such as acrylic acid and (meth)acrylonitrile; epoxy-containing monomers such as glycidyl (meth)acrylate and methylglycidyl (meth)acrylate; sulfonic acid-containing monomers such as sodium vinyl sulfonate; phosphoric acid-containing monomers; (meth)acrylates having alicyclic hydrocarbon groups such as cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate and isobornyl (meth)acrylate; vinyl esters such as vinyl acetate and vinyl propionate; aromatic vinyl compounds such as styrene and vinyltoluene; olefins or dienes such as ethylene, propylene, butadiene, isoprene and isobutylene; vinyl ethers such as vinyl alkyl ether; and vinyl chloride.
[0082] The total content of the structural unit derived from the other monomer (A2) in the polymer (A) is, for example, 30 wt % or less, or 10 wt % or less, and is preferably 0 wt % (containing no such structural unit).
[0083] The polymer (A) preferably has a glass transition temperature (Tg h ) in the range of -55°C or above, preferably having a structural unit derived from a (meth)acrylic monomer h The structural unit of the (meth)acrylic monomer in the range of -40°C or more preferably has a Tg derived from h The structural unit of the (meth)acrylic monomer preferably has a temperature in the range of -30°C or above and a temperature derived from Tg h The polymer (A) may have at least one selected from the group consisting of a structural unit derived from monomer (A3) and a structural unit derived from a (meth)acrylic monomer having an alkyl group with 1 to 3 carbon atoms in a side chain. By making the polymer (A) have a structural unit derived from a Tg h The structural unit of the (meth)acrylic monomer in the range of -55°C or higher can further improve the durability of the optical layered body 10A.
[0084] The polymer (A) can be formed by polymerizing one or more of the above-mentioned monomers using a known method. Monomers and partial polymers of monomers can also be polymerized. The polymerization can be implemented by, for example, solution polymerization, emulsion polymerization, bulk polymerization, thermal polymerization, and active energy ray polymerization. From the viewpoint of being able to form an adhesive sheet with excellent optical transparency, solution polymerization and active energy ray polymerization are preferred. It is preferred to avoid contact between the monomer and / or partial polymer and oxygen and implement polymerization. For this purpose, polymerization in an inactive gas atmosphere such as nitrogen or polymerization in a state where oxygen is blocked by a resin film or the like can be adopted. The polymer (A) to be formed can be any form of a random copolymer, a block copolymer, a graft copolymer, etc.
[0085] The polymerization system for forming the polymer (A) may contain one or more polymerization initiators. The type of polymerization initiator may be selected according to the polymerization reaction, and may be, for example, a thermal polymerization initiator or a photopolymerization initiator.
[0086] The solvent used in the solution polymerization is, for example, esters such as ethyl acetate and n-butyl acetate; aromatic hydrocarbons such as toluene and benzene; aliphatic hydrocarbons such as n-hexane and n-heptane; alicyclic hydrocarbons such as cyclohexane and methylcyclohexane; ketones such as methyl ethyl ketone and methyl isobutyl ketone, but the solvent is not limited to the above examples. The solvent may be a mixed solvent of two or more solvents.
[0087] The polymerization initiator used in the solution polymerization is, for example, an azo polymerization initiator, a peroxide polymerization initiator, and a redox polymerization initiator. Peroxide polymerization initiators are, for example, dibenzoyl peroxide and tert-butyl permaleate. Among them, the azo polymerization initiator disclosed in Japanese Patent Publication No. 2002-69411 is preferred. The azo polymerization initiator is, for example, 2,2'-azobisisobutyronitrile (AIBN), 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(2-methylpropionic acid) dimethyl ester, 4,4'-azobis(4-cyanovaleric acid), but the polymerization initiator is not limited to the above examples. Relative to 100 parts by weight of the total amount of the monomer, the amount of the azo polymerization initiator is, for example, 0.05 to 0.5 parts by weight, and can also be 0.1 to 0.3 parts by weight.
[0088] The active energy rays used in the active energy ray polymerization are, for example, ionizing rays such as α rays, β rays, γ rays, neutron rays, electron rays, and ultraviolet rays. The active energy rays are preferably ultraviolet rays. Polymerization using ultraviolet irradiation is also called photopolymerization. The polymerization system of active energy ray polymerization typically includes a photopolymerization initiator. The polymerization conditions of the active energy polymerization are not limited as long as the polymer (A) can be formed.
[0089] Photopolymerization initiators include, for example, benzoin ether photopolymerization initiators, acetophenone photopolymerization initiators, α-ketol photopolymerization initiators, aromatic sulfonyl chloride photopolymerization initiators, photoactive oxime photopolymerization initiators, benzoin photopolymerization initiators, benzyl photopolymerization initiators, benzophenone photopolymerization initiators, ketal photopolymerization initiators, and thioxanthone photopolymerization initiators, but the photopolymerization initiators are not limited to the above examples.
[0090] Examples of benzoin ether photopolymerization initiators include benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isopropyl ether, benzoin isobutyl ether, 2,2-dimethoxy-1,2-diphenylethane-1-one, and anisole methyl ether. Examples of acetophenone photopolymerization initiators include 2,2-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 1-hydroxycyclohexyl phenyl ketone, 4-phenoxydichloroacetophenone, and 4-(tert-butyl)dichloroacetophenone. Examples of α-ketoalcohol photopolymerization initiators include 2-methyl-2-hydroxypropiophenone and 1-[4-(2-hydroxyethyl)phenyl]-2-methylpropane-1-one. Examples of aromatic sulfonyl chloride photopolymerization initiators include 2-naphthalenesulfonyl chloride. An example of a photoactive oxime photopolymerization initiator is 1-phenyl-1,1-propanedione-2-(O-ethoxycarbonyl oxime). An example of a benzoin photopolymerization initiator is benzoin. An example of a benzyl photopolymerization initiator is benzyl. An example of a benzophenone photopolymerization initiator is benzophenone, benzoylbenzoic acid, 3,3'-dimethyl-4-methoxybenzophenone, polyvinylbenzophenone, α-hydroxycyclohexylphenylketone. An example of a ketal photopolymerization initiator is benzyldimethylketal. An example of a thioxanthone photopolymerization initiator is thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-diisopropylthioxanthone, and dodecylthioxanthone.
[0091] The amount of the photopolymerization initiator used is, for example, 0.01 to 1 part by weight, or 0.05 to 0.5 part by weight, relative to 100 parts by weight of the total amount of the monomers.
[0092] The weight average molecular weight (Mw) of polymer (A) is, for example, 1 million to 3 million, preferably 1.8 million to 3 million. By making the weight average molecular weight of polymer (A) 1 million to 3 million, there is a tendency to suppress cracks in the adhesive sheet and to suppress the increase in viscosity and the occurrence of gelation. The weight average molecular weight (Mw) of the polymer in this specification is a value (in terms of polystyrene) obtained by measuring based on GPC (gel permeation chromatography).
[0093] The content of the polymer (A) in the adhesive composition (I) is, for example, 50% by weight or more, 60% by weight or more, 70% by weight or more, 75% by weight or more, or 80% by weight or more, in terms of solid content ratio. The upper limit of the content is, for example, 99% by weight or less, 97% by weight or less, or 95% by weight or less.
[0094] <Antistatic Agent>
[0095] The adhesive composition (I) contains an antistatic agent. The adhesive composition (I) may contain one or more antistatic agents. Examples of the antistatic agent are ionic compounds such as salts. The ionic compound may be an ionic liquid that is liquid at normal temperature (25° C.).
[0096] Examples of ionic compounds are inorganic cation salts and organic cation salts. Examples of inorganic cation salts are inorganic cation-anion salts. Examples of cations contained in inorganic cation salts are alkali metal ions. Alkali metal ions are, for example, lithium ions, sodium ions, potassium ions, preferably lithium ions. The inorganic cation salt may be a lithium salt.
[0097] Examples of anions contained in inorganic cationic salts are Cl - Br - ,I - 、AlCl4 - 、Al2Cl7 - 、BF4 - PF6 - 、ClO4 - 、NO3 - 、CH3COO - CF3COO - 、CH3SO3 - CF3SO3 - 、(CF3SO2)3C - 、AsF6 - 、SbF6 - 、NbF6 - 、TaF6 - 、(CN)2N - 、C4F9SO3 - 、C3F7COO - 、(CF3SO2)(CF3CO)N - , - O3S(CF2)3SO3 - , and anions represented by the following general formulas (a) to (d).
[0098] (a) (C n F 2n+1 SO2)2N -(n is an integer from 1 to 10)
[0099] (b) CF2(C m F 2m SO2)2N - (m is an integer from 1 to 10)
[0100] (c) - O3S(CF2) l SO3 - (l is an integer from 1 to 10)
[0101] (d) (C p F 2p+1 SO2)N - (C q F 2q+1 SO2) (p and q are independently integers of 1 to 10)
[0102] The anion contained in the inorganic cation salt is preferably a fluorine-containing anion, and more preferably a fluorine-containing imide anion. An example of the fluorine-containing imide anion is an imide anion having a perfluoroalkyl group. A more specific example of the fluorine-containing imide anion is (CF3SO2)(CF3CO)N - , the anion represented by the above general formula (a), (b) or (d) is preferably (CF3SO2)2N - 、(C2F5SO2)2N - (perfluoroalkylsulfonyl)imide represented by the general formula (a), more preferably (CF3SO2)2N - An example of a preferred inorganic cation salt is lithium bis(trifluoromethanesulfonyl)imide (LiTFSI).
[0103] Examples of organic cation salts are organic cation-anion salts. Examples of cations contained in organic cation salts are organic .organic Contained in Examples are nitrogen , sulfur , containing phosphorus , preferably containing nitrogen , sulfur . Nitrogen Examples are ammonium cations, piperidine Cation, pyrrolidine Cation, pyridine Cation, cation having a pyrroline skeleton, cation having a pyrrole skeleton, imidazole Cation, Tetrahydropyrimidine Cations, dihydropyrimidines Cation, pyrazole Cationic, pyrazoline Cationic. Sulfur An example of a sulfonium cation is a sulfonium cation. An example is Cationic. Organic Examples of organic groups contained in are alkyl, alkoxy, alkenyl. Preferred organic Specific examples are tetraalkylammonium cations (e.g., tributylmethylammonium cations), alkylpiperidinium Cation, alkyl pyrrolidine cation.
[0104] Examples of anions contained in the organic cation salt are the same as those contained in the inorganic cation salt. Preferred examples of organic cation salts are 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide salt (EMI-FSI), trimethylbutylammonium bis(trifluoromethanesulfonyl)imide.
[0105] The antistatic agent may be a combination of an inorganic cation salt and an organic cation salt. The antistatic agent preferably contains an organic cation salt.
[0106] Relative to 100 parts by weight of polymer (A), the amount of the antistatic agent in the adhesive composition (I) is, for example, 0.5 parts by weight or more, and can be 1 part by weight or more, 2 parts by weight or more, 3 parts by weight or more, and further can be 4 parts by weight or more. Relative to 100 parts by weight of polymer (A), the upper limit of the amount is, for example, less than 10 parts by weight, and can be 9 parts by weight or less, 8 parts by weight or less, 7 parts by weight or less, and further can be 6 parts by weight or less. By appropriately adjusting the amount of the antistatic agent in the adhesive composition (I), the durability of the adhesive sheet 1 can be further improved.
[0107] <Free Radical Scavenger>
[0108] The adhesive composition (I) may further contain a radical scavenger. Examples of the radical scavenger include various antioxidants such as hindered phenols, hindered amines, phosphites, phenols, and thioethers, and blends of these systems.
[0109] Examples of antioxidants include free radical chain terminators and peroxide decomposers.
[0110] The antioxidant may be at least one selected from hindered phenols, hindered amines and phosphites.
[0111] The hindered phenol antioxidant may have a structure in which a tert-butyl group is bonded to at least one carbon atom adjacent to a carbon atom on an aromatic ring to which an OH group of phenol is bonded. Examples of hindered phenol antioxidants are butylated hydroxytoluene (BHT); and Irganox 1010, Irganox 1010FF, Irganox 1035, Irganox 1035FF, Irganox 1076, Irganox 1076FD, Irganox 1076DWJ, Irganox 1098, Irganox 1135, Irganox 1330, Irganox 1726, Irganox 1425WL, Irganox 1520L, Irganox 245, Irganox 245FF, Irganox 259, Irganox 3114, Irganox 565 and Irganox 295 (all trade names, manufactured by BASF).
[0112] The hindered amine antioxidant may have at least one hindered piperidinyl group in one molecule. Examples of the hindered amine antioxidant are ADK STAB LA-63, ADK STAB LA-63P, ADK STAB LA-52, and ADK STAB LA-57 (all trade names, manufactured by ADEKA Corporation).
[0113] Examples of the phosphite antioxidant are triphenyl phosphite, diphenyl isodecyl phosphite, and phenyl diisodecyl phosphite; and ADK STAB 2112, ADK STAB 2112RG, ADK STAB 1178, and ADK STAB 3010 (all trade names, manufactured by ADEKA Corporation).
[0114] Examples of phenolic antioxidants include monophenolic antioxidants, bisphenolic antioxidants, and polymeric phenolic antioxidants. Examples of monophenolic antioxidants include 2,6-di-tert-butyl-p-cresol, butylated hydroxyanisole, 2,6-di-tert-butyl-4-ethylphenol, and stearyl β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate. Examples of bisphenol antioxidants are 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 2,2'-methylenebis(4-ethyl-6-tert-butylphenol), 4,4'-thiobis(3-methyl-6-tert-butylphenol), 4,4'-butylidenebis(3-methyl-6-tert-butylphenol), 3,9-bis[1,1-dimethyl-2-[β-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy]ethyl]2,4,8,10-tetraoxaspiro[5,5]undecane. Examples of high molecular weight phenolic antioxidants are 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane, 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, tetrakis[methylene-3-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate]methane, bis[3,3'-bis(4'-hydroxy-3'-tert-butylphenyl)butyrate]ethylene glycol ester, 1,3,5-tris(3',5'-di-tert-butyl-4'-hydroxybenzyl)-S-triazine-2,4,6-(1H,3H,5H)trione and tocopherol.
[0115] Examples of the thioether antioxidant include ADK STAB AO-503 and ADK STAB AO-26 (both trade names, manufactured by ADEKA Corporation).
[0116] The molecular weight of the radical scavenger (e.g., antioxidant) may be 1000 or less, 900 or less, 850 or less, 800 or less, 700 or less, 600 or less, 500 or less, 450 or less, or 400 or less. The lower limit of the molecular weight is, for example, 100 or more. According to the research of the present inventors, the radical scavenger having a molecular weight within the above range is particularly suitable for suppressing the amount of free radicals generated in the adhesive sheet formed by the adhesive composition (I).
[0117] The free radical scavenger (eg, antioxidant) may be a liquid at 25°C.
[0118] The amount of the radical scavenger in the adhesive composition (I) is, for example, 0.1 parts by weight or more, 0.2 parts by weight or more, 0.3 parts by weight or more, 0.4 parts by weight or more, and further 0.5 parts by weight or more, relative to 100 parts by weight of the polymer (A). The upper limit of the amount is, for example, 15 parts by weight or less, 10 parts by weight or less, 7 parts by weight or less, 5 parts by weight or less, less than 5 parts by weight, 4 parts by weight or less, 3 parts by weight or less, and further 2 parts by weight or less.
[0119] <Additives>
[0120] Adhesive composition (I) may further include materials other than polymer (A), antistatic agent and free radical scavenger. Examples of such materials are additives. Examples of additives are crosslinking agents, silane coupling agents, colorants such as pigments and dyes, ultraviolet absorbers, surfactants, plasticizers, tackifiers, surface lubricants, leveling agents, re-operation improvers, softeners, inhibitors, rust inhibitors, inorganic fillers, organic fillers, powders such as metal powders, particles, and foils. Relative to 100 parts by weight of polymer (A), for example, additives can be combined in a total of less than 10 parts by weight, preferably less than 5 parts by weight, and more preferably less than 3 parts by weight.
[0121] Examples of crosslinking agents are organic crosslinking agents and multifunctional metal chelates. Examples of organic crosslinking agents are isocyanate crosslinking agents, peroxide crosslinking agents, epoxy crosslinking agents and imine crosslinking agents. Organic crosslinking agents and multifunctional metal chelates can be used for any type of adhesive composition (I) in solvent-based and active energy ray-cured types. When the adhesive composition (I) is solvent-based, the crosslinking agent is preferably a peroxide crosslinking agent and an isocyanate crosslinking agent. Peroxide crosslinking agents and isocyanate crosslinking agents can also be used in combination. The adhesive composition (I) can include an isocyanate crosslinking agent, a peroxide crosslinking agent, and both an isocyanate crosslinking agent and a peroxide crosslinking agent.
[0122] Examples of isocyanate crosslinking agents include aromatic isocyanate compounds such as toluene diisocyanate, chlorophenylene diisocyanate, diphenylmethane diisocyanate, xylene diisocyanate, and polymethylene polyphenyl isocyanate; alicyclic isocyanate compounds such as cyclopentylene diisocyanate, cyclohexylene diisocyanate, hydrogenated diphenylmethane diisocyanate, and isophorone diisocyanate; and aliphatic isocyanate compounds such as butylene diisocyanate, tetramethylene diisocyanate, and hexamethylene diisocyanate. Isocyanate crosslinking agents may be compounds (adducts) obtained by adding the above isocyanate compounds to polyol compounds such as trimethylolpropane; compounds obtained by adding the above isocyanate compounds to polyols such as polyether polyols, polyester polyols, acrylic polyols, polybutadiene polyols, and polyisoprene polyols; and derivatives of the above isocyanate compounds such as isocyanurates. Specific examples of the derivatives include trimethylolpropane / toluene diisocyanate trimer adducts (e.g., Coronate L manufactured by Tosoh Corporation), trimethylolpropane / hexamethylene diisocyanate trimer adducts (e.g., Coronate HL manufactured by Tosoh Corporation), and isocyanurate of hexamethylene diisocyanate (e.g., Coronate HX manufactured by Tosoh Corporation).
[0123] When the adhesive composition (I) contains an isocyanate crosslinking agent, its blending amount is, for example, 0.1 to 10 parts by weight, 0.2 to 5 parts by weight, 0.25 to 3 parts by weight, 0.3 to 1 part by weight, or further 0.3 to 0.5 parts by weight, relative to 100 parts by weight of the polymer (A).
[0124] Examples of peroxide crosslinking agents include di(2-ethylhexyl) peroxydicarbonate, di(4-tert-butylcyclohexyl) peroxydicarbonate, di-sec-butyl peroxydicarbonate, tert-butyl peroxyneodecanoate, tert-hexyl peroxypivalate, tert-butyl peroxypivalate, dilauroyl peroxide, di-n-octanoyl peroxide, 1,1,3,3-tetramethylbutyl peroxy-2-ethylhexanoate, di(4-methylbenzoyl) peroxide, benzoyl peroxide, tert-butyl peroxyisobutyrate, and 1,1-di(tert-hexyl peroxide)cyclohexane. The peroxide crosslinking agent may be benzoyl peroxide due to its excellent crosslinking reaction efficiency.
[0125] When the adhesive composition (I) contains a peroxide crosslinking agent, the amount thereof added is, for example, 0.005 to 5 parts by weight, 0.01 to 3 parts by weight, 0.05 to 2 parts by weight, 0.07 to 1 part by weight, 0.07 to 0.5 parts by weight, 0.07 to 0.3 parts by weight, and further 0.07 to 0.2 parts by weight, relative to 100 parts by weight of the polymer (A).
[0126] Examples of the silane coupling agent include epoxy group-containing silane coupling agents such as 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; amino group-containing silane coupling agents such as 3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, 3-triethoxysilyl-N-(1,3-dimethylbutylene)propylamine, and N-phenyl-γ-aminopropyltrimethoxysilane; (meth)acryl group-containing silane coupling agents such as 3-acryloxypropyltrimethoxysilane and 3-methacryloxypropyltriethoxysilane; and isocyanate group-containing silane coupling agents such as 3-isocyanatepropyltriethoxysilane.
[0127] When the adhesive composition (I) contains a silane coupling agent, the amount thereof is, for example, 5 parts by weight or less, 3 parts by weight or less, 1 part by weight or less, 0.5 parts by weight or less, 0.2 parts by weight or less, 0.1 parts by weight or less, and further 0.05 parts by weight or less, relative to 100 parts by weight of the polymer (A). The adhesive composition (I) may not contain a silane coupling agent.
[0128] The type of adhesive composition (I) is, for example, an emulsion type, a solvent type (solution type), an active energy ray curable type (photocurable type), and a hot melt type (hot melt type). From the viewpoint of being able to form an adhesive sheet with excellent durability, the adhesive composition (I) may be a solvent type or an active energy ray curable type, or may be a solvent type. The solvent type adhesive composition (I) may not contain a photocuring agent such as an ultraviolet curing agent.
[0129] The adhesive composition (I) can be used, for example, in an optical laminate. In other words, the adhesive composition (I) can be an adhesive composition for an optical laminate. It should be noted that the use of the adhesive composition (I) is not limited to the above examples.
[0130] In the present embodiment, when the polymer (A) is formed by the above-mentioned monomer combination, the glass transition temperature Tg of the polymer (A) calculated according to the FOX formula can be below -40°C. The glass transition temperature Tg of the polymer (A) tends to be related to the glass transition temperature of the adhesive sheet 1. By making the glass transition temperature Tg of the polymer (A) below -40°C, for example, the free volume of the polymer (A) contained in the adhesive sheet is not easy to decrease even in a low temperature environment. If the free volume of the polymer (A) is not easy to decrease, it is easy to generate a space in the adhesive sheet 1 where the antistatic agent can move. As a result, the antistatic agent is easy to move in the adhesive sheet 1, which can further suppress the increase in surface resistivity. In addition, by making the glass transition temperature Tg of the polymer (A) below -40°C, for example, the optical laminate 10A can further suppress the increase in surface resistivity on the side of the adhesive sheet 1, for example, in a low temperature environment. That is, the ratio R / R1 can be further reduced.
[0131] The glass transition temperature Tg is, for example, -40°C or less, -44°C or less, further -45°C or less, or -50°C or less. The lower limit of the glass transition temperature Tg is, for example, -70°C or -60°C. The FOX formula can be represented by the following formula.
[0132] 1 / Tg=w1 / Tg1+w2 / Tg2+···+w m / Tg m
[0133] In the above formula, Tg is the glass transition temperature [K] of the polymer (A). m are the weight fractions of the monomers in the monomer group. m are the glass transition temperatures [K] of the homopolymers of the respective monomers. m is a positive integer. As an example, w1 is the weight fraction of the first monomer in the monomer group, and Tg1 is the glass transition temperature [K] of the homopolymer of the first monomer. By calculating the glass transition temperature [K] of the polymer (A) by the above formula and converting the units, the glass transition temperature Tg [°C] of the polymer (A) can be calculated.
[0134] [Antistatic layer]
[0135] The antistatic layer 2 is a layer containing a conductive material. The conductive material may be a material other than ITO, such as a conductive polymer, a composite of a conductive polymer and a dopant, an ionic surfactant, conductive fine particles, an ionic compound, and the like.
[0136] As the conductive polymer, for example, polythiophene, polyaniline, polypyrrole, polyquinoxaline, polyacetylene, polystyrene, polynaphthalene and their derivatives can be cited. The conductive material can contain one or more of these conductive polymers. As the conductive polymer, polythiophene, polyaniline and their derivatives are preferably used, and polythiophene derivatives are particularly preferably used. Polythiophene, polyaniline and their derivatives function as water-soluble or water-dispersible conductive polymers, for example. In the case where the conductive polymer is water-soluble or water-dispersible, an aqueous solution or aqueous dispersion of the conductive polymer can be used to make the antistatic layer 2. In this case, the production of the antistatic layer 2 does not require the use of a non-aqueous organic solvent, and therefore, the denaturation of the optical film 3, etc. caused by the organic solvent can be suppressed.
[0137] The conductive polymer may also have a hydrophilic functional group. Examples of the hydrophilic functional group include a sulfonic group, an amino group, an amide group, an imino group, a hydroxyl group, a thiol group, a hydrazine group, a carboxyl group, a sulfate group, a phosphate group, and salts thereof (e.g., a quaternary ammonium salt group). When the conductive polymer has a hydrophilic functional group, there is a tendency that the conductive polymer is easily dissolved in water, or that the conductive polymer in a microparticle form is easily dispersed in water.
[0138] From the viewpoint of conductivity and chemical stability, the conductive polymer is preferably poly(3,4-disubstituted thiophene). Examples of poly(3,4-disubstituted thiophene) include poly(3,4-alkylenedioxythiophene) and poly(3,4-dialkoxythiophene), preferably poly(3,4-alkylenedioxythiophene). Poly(3,4-alkylenedioxythiophene) has a structural unit represented by the following formula (I).
[0139] [Chemical formula 4]
[0140]
[0141] In formula (I), R 1 For example, it is an alkylene group having 1 to 4 carbon atoms. The alkylene group may be linear or branched. Examples of the alkylene group include methylene, 1,2-ethylene, 1,3-propylene, 1,4-butylene, 1-methyl-1,2-ethylene, 1-ethyl-1,2-ethylene, 1-methyl-1,3-propylene and 2-methyl-1,3-propylene, preferably methylene, 1,2-ethylene, 1,3-propylene, and more preferably 1,2-ethylene. The conductive polymer is preferably poly(3,4-alkylenedioxythiophene) (PEDOT).
[0142] As a dopant, for example, polyanions can be mentioned. When the conductive polymer is polythiophene (or its derivatives), the polyanion can form an ion pair with the polythiophene (or its derivatives), so that the polythiophene (or its derivatives) can be stably dispersed in water. As polyanions, there are no special restrictions, and examples include: carboxylic acid polymers such as polyacrylic acid, polymaleic acid, and polymethacrylic acid; sulfonic acid polymers such as polystyrene sulfonic acid, polyvinyl sulfonic acid, and polyisoprene sulfonic acid. The polyanion can be a copolymer of vinyl carboxylic acid or vinyl sulfonic acid and other monomers. As other monomers, for example, (meth)acrylate compounds; aromatic vinyl compounds such as styrene and vinylnaphthalene. The polyanion is particularly preferably polystyrene sulfonic acid (PSS). As a composite of a conductive polymer and a dopant, for example, a composite of poly(3,4-alkylenedioxythiophene) and polystyrene sulfonic acid (PEDOT / PSS) can be mentioned.
[0143] Examples of the ionic surfactant include quaternary ammonium salt type, Cationic surfactants such as onium salt type and sulfonium salt type; anionic surfactants such as carboxylic acid type, sulfonate type, sulfate type, phosphate type, and phosphite type; zwitterionic surfactants such as sulfonobetaine type, alkyl betaine type, and alkyl imidazole betaine type; non-ionic surfactants such as polyol derivatives, β-cyclodextrin inclusion complexes, sorbitan fatty acid monoesters, sorbitan fatty acid diesters, polyoxyalkylene derivatives, and amine oxides.
[0144] As conductive particles, for example, metal oxide particles of tin oxide, antimony oxide, indium oxide, zinc oxide, etc. can be cited, preferably tin oxide particles. As materials of tin oxide particles, for example, tin oxide, antimony-doped tin oxide, indium-doped tin oxide, aluminum-doped tin oxide, tungsten-doped tin oxide, titanium oxide-cerium oxide-tin oxide complex, titanium oxide-tin oxide complex, etc. can be cited. The average particle size of the conductive particles is, for example, 1 to 100 nm, preferably 2 to 50 nm. The average particle size of the conductive particles refers to, for example, a particle size (d50) equivalent to 50% of the volume accumulation in a particle size distribution measured by a laser diffraction particle size analyzer or the like.
[0145] As the ionic compound, for example, the ionic compounds described in the above-mentioned <Antistatic Agent> can be used.
[0146] Other examples of conductive materials include: carbon materials such as acetylene black, Ketjen black, natural graphite, artificial graphite, and carbon nanotubes (CNTs); titanium black; homopolymers of monomers having cationic conductive groups such as quaternary ammonium salts, zwitterionic conductive groups such as betaine compounds, anionic conductive groups such as sulfonates, or non-ionic conductive groups such as glycerol, or copolymers of the monomers with other monomers (for example, ionically conductive polymers such as polymers having structural units derived from acrylates or methacrylates having quaternary ammonium salt groups); materials obtained by alloying hydrophilic polymers such as copolymers of ethylene and methacrylates with acrylic resins, etc. (permanent antistatic agents).
[0147] From the perspective of transparency, total light transmittance, appearance, antistatic effect, and the stability of the antistatic effect in a high temperature or humid environment, the antistatic layer 2 preferably includes at least one selected from a conductive polymer and a carbon material, and more preferably includes a carbon material. Carbon materials are not easy to decompose in a high temperature and high humidity environment and / or under ultraviolet irradiation. Therefore, by making the antistatic layer 2 include a carbon material, weather resistance can be improved. In addition, by making the antistatic layer 2 include a carbon material, the optical laminate 10A can further suppress the rise of the surface resistivity of the adhesive sheet 1 side even in, for example, a low temperature environment. That is, the ratio R / R1 can be further reduced.
[0148] The antistatic layer 2 may further contain other materials such as adhesives in addition to the conductive material. The adhesive, for example, tends to improve the film-forming property of the conductive material and improve the adhesion and bonding (anchoring force) of the antistatic layer 2 to the optical film 3. Examples of the adhesive include: Oxazoline polymers, polyurethane resins, polyester resins, acrylic resins, polyether resins, cellulose resins, polyvinyl alcohol resins, epoxy resins, polyvinyl pyrrolidone, polystyrene resins, polyethylene glycol, pentaerythritol, etc., preferably containing The antistatic layer 2 may include one or more of the adhesives, such as oxazoline polymers, polyurethane resins, polyester resins, acrylic resins, and particularly preferably polyurethane resins. The antistatic layer 2 may include one or more of these adhesives. The content of the adhesive in the antistatic layer 2 is, for example, 1% to 90% by weight, preferably 10% to 80% by weight.
[0149] In the optical laminate 10A, the surface resistivity of the antistatic layer 2 at 25° C. is, for example, 3.0×10 8 Ω / □ or less. By making the surface resistivity of the antistatic layer 2 at 25°C be, for example, 3.0×10 8Ω / □ or less, even in an environment where static electricity is easily generated, poor display caused by charging of a liquid crystal display device having an optical laminate 10A can be further prevented. The surface resistivity of the antistatic layer 2 can be determined by the following method. First, a laminate with the surface of the antistatic layer 2 exposed to the outside is prepared. As such a laminate, for example, a laminate L1 composed of an optical film 3 and an antistatic layer 2 can be cited. Next, the surface resistivity of the antistatic layer 2 in the prepared laminate is measured. The surface resistivity of the antistatic layer 2 can be measured using Hiresta MCP-HT800 (Mitsubishi Chemical Analytech) based on the method specified in JISK6911:1995.
[0150] The surface resistivity of the antistatic layer 2 is preferably 2.0×10 8 Ω / □ or less, more preferably less than 1.0×10 8 Ω / □, more preferably 7.0×10 7 Ω / □ or less, particularly preferably 5.0×10 7 Ω / □ or less. The lower limit of the surface resistivity of the antistatic layer 2 is, for example, 1.0×10 2 Ω / □, further 1.0×10 5 Ω / □, especially 1.0×10 7 Ω / □. When the optical laminate 10A is used in a liquid crystal display device having a touch sensor or a touch panel, the surface resistivity of the antistatic layer 2 may be greater than 1.0×10 7 Ω / □.
[0151] The thickness of the antistatic layer 2 is, for example, 5nm to 180nm, preferably below 150nm, more preferably below 140nm, and can be below 100nm as the case may be. The thickness of the antistatic layer 2 can be more than 10nm, more than 20nm, more than 50nm, and further can be more than 55nm. In order to suppress the rise of the surface resistivity in the low temperature zone, it can be more than 70nm, and can be more than 100nm as the case may be. By properly adjusting the thickness of the antistatic layer 2, the antistatic effect can be further improved. In addition, by properly adjusting the thickness of the antistatic layer 2, the value of the ratio R / R1 of the optical laminate 10A can be further reduced.
[0152] [Optical film]
[0153] The optical film 3 includes, for example, at least one selected from a polarizing film and a retardation film. The optical film 3 may be a laminated film including a polarizing film and / or a retardation film. The optical film 3 may include a film made of glass.
[0154] The polarizing film includes a polarizer. Typically, the polarizing film includes a polarizer and a protective film (transparent protective film). The protective film is, for example, arranged in contact with the main surface of the polarizer. The polarizer can be arranged between two protective films. The protective film can be arranged on at least one side of the polarizer.
[0155] The polarizer is not particularly limited, and examples thereof include: a polarizer obtained by adsorbing a dichroic substance such as iodine and a dichroic dye on a hydrophilic polymer film such as a polyvinyl alcohol film, a partially formalized polyvinyl alcohol film, and a partially saponified film of an ethylene-vinyl acetate copolymer, and then uniaxially stretching the film; a polyene oriented film such as a dehydrated product of polyvinyl alcohol and a dehydrochlorinated product of polyvinyl chloride, etc. The polarizer is typically formed of a polyvinyl alcohol film (polyvinyl alcohol films include partially saponified films of ethylene-vinyl acetate copolymers) and a dichroic substance such as iodine.
[0156] The thickness of the polarizer is not particularly limited, for example, it is 80 μm or less, it can be 50 μm or less, 30 μm or less, 25 μm or less, and further can be 20 μm or less. The lower limit of the thickness of the polarizer is not particularly limited, for example, it is 1 μm or more, it can be 5 μm or more, 10 μm or more, and further can be 15 μm or more. A thin polarizer (for example, a thickness of 20 μm or less) can suppress dimensional changes and contribute to the durability of the optical laminate, especially the durability at high temperatures.
[0157] As the material of the protective film, for example, thermoplastic resins with excellent transparency, mechanical strength, thermal stability, moisture barrier properties, isotropy, etc. can be used. Specific examples of such thermoplastic resins include cellulose resins such as cellulose triacetate, polyester resins, polyethersulfone resins, polysulfone resins, polycarbonate resins, polyamide resins, polyimide resins, polyolefin resins, (meth)acrylic resins, cyclic polyolefin resins (norbornene resins), polyarylate resins, polystyrene resins, polyvinyl alcohol resins, and mixtures thereof. The material of the protective film can be a thermosetting resin or ultraviolet curing resin such as (meth)acrylic acid, urethane, acrylic urethane, epoxy, silicone, etc. In the case where the polarizing film has two protective films, the materials of the two protective films can be the same or different from each other. For example, a protective film formed of a thermoplastic resin can be bonded to one main surface of the polarizer via an adhesive, and a protective film formed of a thermosetting resin or an ultraviolet curing resin can be bonded to the other main surface of the polarizer. The protective film can contain one or more arbitrary additives. Examples of the additive include ultraviolet absorbers, antioxidants, lubricants, plasticizers, mold release agents, anti-coloring agents, flame retardants, nucleating agents, antistatic agents, pigments, and colorants.
[0158] The thickness of the protective film can be appropriately determined, and is generally about 10 to 200 μm in consideration of strength, workability such as handling properties, and thin film properties.
[0159] The polarizer and the protective film are usually bonded together via a water-based adhesive or the like. Examples of the water-based adhesive include isocyanate adhesives, polyvinyl alcohol adhesives, gelatin adhesives, vinyl latex, water-based polyurethane, and water-based polyester. Other adhesives other than the above-mentioned adhesives include ultraviolet curing adhesives and electron beam curing adhesives. Electron beam curing polarizer adhesives show suitable adhesion to various protective films. The adhesive may also contain a metal compound filler.
[0160] In the polarizing film, a retardation film or the like may be formed on the polarizer instead of the protective film. Another protective film or a retardation film or the like may be further provided on the protective film.
[0161] The protective film may be provided with a hard coat layer on the surface opposite to the surface to be bonded to the polarizer, or may be subjected to treatment for the purpose of anti-reflection, anti-sticking, diffusion, anti-glare, etc.
[0162] The polarizing film may be a circular polarizing film.
[0163] As the retardation film, a retardation film obtained by stretching a polymer film or a retardation film obtained by orienting and fixing a liquid crystal material can be used. The retardation film has birefringence in the plane and / or in the thickness direction, for example.
[0164] Examples of the phase difference film include: a phase difference film for antireflection (see Japanese Patent Application Publication No. 2012-133303
[0221] ,
[0222] , and
[0228] ), a phase difference film for viewing angle compensation (see Japanese Patent Application Publication No. 2012-133303
[0225] and
[0226] ), and a tilted orientation phase difference film for viewing angle compensation (see Japanese Patent Application Publication No. 2012-133303
[0227] ).
[0165] The retardation film may have substantially the above-mentioned functions, and is not particularly limited in terms of, for example, retardation value, arrangement angle, three-dimensional birefringence, single layer or multilayer, and the like, and a known retardation film may be used.
[0166] The thickness of the retardation film is preferably 20 μm or less, more preferably 10 μm or less, further preferably 1 to 9 μm, and particularly preferably 3 to 8 μm.
[0167] The phase difference film may be composed of two layers of a quarter wave plate and a half wave plate obtained by aligning and fixing a liquid crystal material, for example.
[0168] [Method for producing optical layered body]
[0169] The optical laminate 10A includes, for example, preparing a laminate L2 including a substrate and a pressure-sensitive adhesive sheet 1 , preparing a laminate L1 including an optical film 3 and an antistatic layer 2 , and transferring the pressure-sensitive adhesive sheet 1 of the laminate L2 onto the antistatic layer 2 of the laminate L1 .
[0170] (Method for Manufacturing Laminated Body L1)
[0171] First, a solution or dispersion of a conductive material is prepared. The solvent of the solution or dispersion is, for example, water, and may further contain a water-soluble organic solvent. Examples of the water-soluble organic solvent include alcohols such as methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, sec-butanol, tert-butanol, n-pentanol, isopentanol, sec-pentanol, tert-pentanol, 1-ethyl-1-propanol, 2-methyl-1-butanol, n-hexanol, and cyclohexanol.
[0172] Next, a solution or dispersion of a conductive material is applied to the surface of the optical film 3. The obtained coating film is dried to form the antistatic layer 2 on the optical film 3. Thus, a laminate L1 composed of the optical film 3 and the antistatic layer 2 is obtained.
[0173] (Method for Manufacturing Laminated Body L2)
[0174] The pressure-sensitive adhesive sheet 1 is formed from the pressure-sensitive adhesive composition (I). The pressure-sensitive adhesive sheet 1 includes, for example, a cross-linked product of a (meth)acrylic polymer. The pressure-sensitive adhesive sheet 1 is formed from the pressure-sensitive adhesive composition (I) by the following method.
[0175] The method for manufacturing the adhesive sheet 1 includes, for example, applying the adhesive composition (I) to a substrate to form a coating film; and drying the obtained coating film. By drying the coating film, an adhesive sheet 1 is formed on the substrate. Thus, a laminate L2 consisting of the substrate and the adhesive sheet 1 is obtained.
[0176] As the substrate, for example, a release film can be used. The pressure-sensitive adhesive sheet 1 formed on the release film can be transferred to, for example, an optical film or the like. The substrate can be an optical film.
[0177] The release film can be used as a release liner after the pressure-sensitive adhesive sheet 1 is transferred to the antistatic layer 2 until the pressure-sensitive adhesive sheet 1 is actually used, thereby simplifying the process.
[0178] As the constituent material of the release film, for example, plastic film, porous materials such as paper, cloth, nonwoven fabric, net, foam sheet, metal foil, and appropriate thin sheets such as laminates thereof can be preferably used. Plastic film is preferably used because of its excellent surface smoothness.
[0179] The plastic film is not particularly limited, and examples thereof include polyethylene films, polypropylene films, polybutene films, polybutadiene films, polymethylpentene films, polyvinyl chloride films, vinyl chloride copolymer films, polyethylene terephthalate films, polybutylene terephthalate films, polyurethane films, and ethylene-vinyl acetate copolymer films.
[0180] The thickness of the release film is usually 5 to 200 μm, preferably about 5 to 100 μm. The release film is subjected to release treatments such as silicone, fluorine, and long-chain alkyl. The release film may be subjected to release and antifouling treatments using a fatty acid amide-based release agent, silica powder, or the like, or antistatic treatments such as coating, mixing, and vapor deposition.
[0181] A solution (adhesive solution) containing the adhesive composition (I) can be applied to the substrate. The solid content concentration of the adhesive solution is, for example, 5 to 50% by weight, preferably 10 to 40% by weight. It should be noted that the adhesive solution can be prepared by appropriately adding a solvent that is the same as the polymerization solvent or a different solvent to the adhesive composition (I) corresponding to the polymerization method of the (meth)acrylic polymer (A).
[0182] As a method for applying the adhesive composition (I) to the substrate, various methods can be used, for example, roll coating, lick roller coating, gravure coating, reverse coating, roller brushing, spray coating, dip roll coating, rod coating, blade coating, air knife coating, curtain coating, die lip coating, extrusion coating using a die coater, etc. The amount of the adhesive composition (I) applied can be appropriately adjusted according to the target thickness of the adhesive sheet 1.
[0183] The coating film is dried to cure the coating film, thereby forming the adhesive sheet 1. The drying temperature of the coating film is, for example, 130°C or less, preferably 125°C or less, more preferably 120°C or less, further preferably 110°C or less, and particularly preferably 100°C or less. The drying temperature of the coating film may be 60°C or more, or 80°C or more. When the drying temperature is 60°C or more, there is a tendency that, for example, the reaction of the isocyanate crosslinking agent proceeds smoothly, thereby being able to increase the cohesive force of the adhesive sheet 1 and reducing the display unevenness of the image display device. When the drying temperature is 130°C or less, there is a tendency that, for example, the reaction rate of the isocyanate crosslinking agent can be appropriately adjusted and transparency can be ensured.
[0184] The drying time of the coating film can be appropriately adjusted according to the composition of the adhesive composition (I), and is preferably 30 to 300 seconds, more preferably 40 to 240 seconds, and particularly preferably 60 to 180 seconds.
[0185] The thickness of the adhesive sheet 1 is not particularly limited, and may be 2 to 150 μm, 2 to 100 μm, or 5 to 50 μm. By appropriately adjusting the thickness of the adhesive sheet 1, the adhesion between the adhesive sheet 1 and the antistatic layer 2 can be improved. In addition, by appropriately adjusting the thickness of the adhesive sheet 1, the adhesive sheet 1 can be prevented from peeling off from adherends such as glass and image display devices.
[0186] The pressure-sensitive adhesive sheet 1 of the laminate L2 obtained above is transferred onto the antistatic layer 2 of the laminate L1. Thus, an optical laminate 10A including the optical film 3, the antistatic layer 2, and the pressure-sensitive adhesive sheet 1 is obtained.
[0187] Figure 2 FIG. 2 is a cross-sectional view schematically showing another example of the optical layered body of the present embodiment. Figure 2 As shown, the optical laminate 10B has a laminated structure in which a release liner 4, an adhesive sheet 1, an antistatic layer 2, and an optical film 3 are laminated in this order. The optical laminate 10B can be used by being attached to, for example, an image display unit after peeling off the release liner 4. The following examples can be combined with each other as long as they are not technically contradictory.
[0188] Examples of the material constituting the release liner 4 include plastic films such as polyethylene, polypropylene, polyethylene terephthalate, and polyester films, porous materials such as paper, cloth, and nonwoven fabrics, nets, foam sheets, metal foils, and appropriate thin sheets such as laminates thereof. Plastic films are preferably used because of their excellent surface smoothness.
[0189] The plastic film is not particularly limited as long as it can protect the adhesive sheet 1, and examples thereof include polyethylene films, polypropylene films, polybutylene films, polybutadiene films, polymethylpentene films, polyvinyl chloride films, vinyl chloride copolymer films, polyethylene terephthalate films, polybutylene terephthalate films, polyurethane films, and ethylene-vinyl acetate copolymer films.
[0190] The thickness of the release liner 4 is usually 5 to 200 μm, preferably about 5 to 100 μm. If necessary, the release liner 4 may be subjected to mold release and antifouling treatment using silicone, fluorine, long-chain alkyl or fatty acid amide release agents, silica powder, etc., or antistatic treatment such as coating, mixing, or vapor deposition. In particular, by appropriately subjecting the surface of the release liner 4 to a release treatment such as silicone treatment, long-chain alkyl treatment, or fluorine treatment, the releasability from the pressure-sensitive adhesive sheet 1 can be further improved.
[0191] As described above, the release film used when producing the pressure-sensitive adhesive sheet 1 may be used as the release liner 4 .
[0192] The optical laminate of the present embodiment can be circulated and stored in the form of a winding body formed by winding a strip-shaped optical laminate, or in the form of a monolithic optical laminate. The optical laminate of the present embodiment is suitable for image display devices used in environments that are particularly prone to static electricity, especially for vehicle-mounted displays. As vehicle-mounted displays, for example, instrument panels for car navigation devices, instrument clusters (cluster panels), mirror displays, etc. The instrument cluster is a panel that displays the driving speed of the vehicle, the speed of the engine, etc.
[0193] [Embodiments of Image Display Panel]
[0194] Figure 3 FIG. 1 is a cross-sectional view schematically showing an example of an image display panel according to the present embodiment. Figure 3 As shown, the image display panel 11A includes the optical layered body 10A and further includes, for example, the image display unit 30A. Specifically, the optical layered body 10A is bonded to the image display unit 30A via the pressure-sensitive adhesive sheet 1 .
[0195] The image display unit 30A includes, for example, an image forming layer 32, a first transparent substrate 31, and a second transparent substrate 33. The image forming layer 32 is, for example, disposed between the first transparent substrate 31 and the second transparent substrate 33, and is in contact with the first transparent substrate 31 and the second transparent substrate 33. The adhesive sheet 1 of the optical laminate 10A is in contact with, for example, the first transparent substrate 31 of the image display unit 30A.
[0196] The image forming layer 32 is, for example, a liquid crystal layer containing liquid crystal molecules that are uniformly oriented in the absence of an electric field. A liquid crystal layer containing such liquid crystal molecules is suitable for an IPS (In-Plane-Switching) method. However, the liquid crystal layer can also be used for a TN (Twisted Nematic) type, an STN (Super Twisted Nematic) type, a π type, a VA (Vertical Alignment) type, and the like. In this specification, an image display unit having a liquid crystal layer is sometimes referred to as a liquid crystal unit, and an image display panel having a liquid crystal unit is sometimes referred to as a liquid crystal panel. It should be noted that the image forming layer 32 can also be an EL light-emitting layer.
[0197] The thickness of the image forming layer 32 is, for example, 1.5 μm to 4 μm.
[0198] As materials of the first transparent substrate 31 and the second transparent substrate 33, glass and polymers can be cited, for example. In this specification, a transparent substrate composed of a polymer is sometimes referred to as a polymer film. As polymers constituting the transparent substrate, for example, polyethylene terephthalate, polycycloolefin, polycarbonate, etc. can be cited. The thickness of the transparent substrate composed of glass is, for example, 0.1 mm to 1 mm. The thickness of the transparent substrate composed of a polymer is, for example, 10 μm to 200 μm.
[0199] The image display unit 30A may further include other layers in addition to the image forming layer 32, the first transparent substrate 31, and the second transparent substrate 33. As other layers, for example, a color filter, an easy adhesion layer, and a hard coating layer can be cited. The color filter is, for example, arranged closer to the visible side than the image forming layer 32, preferably between the first transparent substrate 31 and the adhesive sheet 1 of the optical laminate 10A. The easy adhesion layer and the hard coating layer are, for example, arranged on the surface of the first transparent substrate 31 or the second transparent substrate 33.
[0200] The image display panel 11A may also further include other components in addition to the optical stack 10A and the image display unit 30A. For example, the image display panel 11A may further include a conductive structure (not shown) electrically connected to the side of the optical stack 10A. If the conductive structure is grounded, it is easy to suppress the optical stack 10A from being charged due to static electricity. The conductive structure may cover the entire side of the optical stack 10A, or may partially cover the side of the optical stack 10A. The ratio of the area of the side of the optical stack 10A covered by the conductive structure to the area of the entire side of the optical stack 10A is, for example, 1% or more, preferably 3% or more.
[0201] Examples of the material of the conductive structure include conductive pastes made of metals such as silver and gold, conductive adhesives, and other conductive materials. The conductive structure may be wiring extending from the side surface of the optical laminate 10A.
[0202] The image display panel 11A may further include other optical films in addition to the optical film 3. Examples of other optical films include polarizing plates, reflective plates, anti-transmission plates, viewing angle compensation films, brightness enhancement films, and other films that can be used in image display devices. The image display panel 11A may include one or two or more of these other optical films.
[0203] When the other optical film is a polarizing plate, the polarizing plate can be bonded to the second transparent substrate 33 of the image display unit 30A via an adhesive sheet, for example. The polarizing plate has, for example, the structure described above for the optical film 3. In the polarizing plate as the other optical film, the transmission axis (or absorption axis) of the polarizer is, for example, orthogonal to the transmission axis (or absorption axis) of the polarizer in the polarizing plate 2. As the material of the adhesive sheet for bonding the polarizing plate to the second transparent substrate 33, the material described above for the adhesive sheet 1 can be used. The thickness of the adhesive sheet is not particularly limited, and is, for example, 1 to 100 μm, preferably 2 to 50 μm, more preferably 2 to 40 μm, and further preferably 5 to 35 μm.
[0204] Figure 4 FIG. 2 is a cross-sectional view schematically showing another example of an image display panel of the present embodiment. Figure 4 As shown, the image display panel 11B further includes a conductive layer 40 disposed between the optical laminate 10A and the image display unit 30A. However, the image display panel is preferably an image display panel 11A that does not include a conductive layer 40. In the image display panel 11B provided with a conductive layer 40, there is a tendency for the reflectivity to increase, which sometimes leads to a reduction in the visual recognition of the display. In the image display panel 11A that does not include a conductive layer 40, a conductive portion (the conductive structure described above) adjacent to the adhesive sheet 1 is preferably provided. As a conductive portion, for example, a conductive silver paste can be used. After the optical laminate 10A is attached to the image display unit 30A, a conductive silver paste or the like is applied to the side portion of the adhesive sheet 1 to provide a conductive portion so that it is connected thereto with other wiring, the frame of the image display device, etc., thereby being able to improve the antistatic property of the image display panel.
[0205] The conductive layer 40 is, for example, a layer containing a conductive agent. As the conductive agent, metal oxides, conductive polymers, the conductive agents described above for the adhesive sheet 1 and the antistatic layer 2, etc. can be used. The thickness of the conductive layer 40 is, for example, 5 nm to 180 nm. The surface resistivity of the conductive layer 40 is, for example, 1.0×10 6 Ω / □~1.0×10 10 Ω / □, preferably 1.0×10 8 Ω / □~1.0×10 9 Ω / □.
[0206] The image display panel of this embodiment may also be an image display panel with a built-in touch sensor function. Figure 5 . Figure 5 FIG. 2 is a cross-sectional view schematically showing another example of an image display panel of the present embodiment. Figure 5As shown, the image display panel 11C has an image display unit 30B further including a touch sensing electrode portion 35. In the image display unit 30B, the touch sensing electrode portion 35 is arranged between the first transparent substrate 31 and the second transparent substrate 33. The touch sensing electrode portion 35 has the functions of a touch sensor and a touch drive. The image display panel 11C is a so-called embedded image display panel, and the image display unit 30B is a so-called embedded image display unit. However, it should be noted that, in the image display unit 30B, the touch sensing electrode portion 35 can also be arranged closer to the visible side than the first transparent substrate 31. That is, the image display panel 11C can be a so-called embedded image display panel, and the image display unit 30B can be a so-called embedded image display unit.
[0207] The touch sensing electrode portion 35 includes, for example, a touch sensor electrode 36 and a touch drive electrode 37. The touch sensor electrode 36 refers to a (receiving) electrode for touch detection. The touch sensor electrode 36 and the touch drive electrode 37 can be independently formed by various patterns. For example, when the image display unit 30B is in the form of a flat plate, the touch sensor electrode 36 and the touch drive electrode 37 can be independently arranged in the X-axis direction and the Y-axis direction, respectively, to form a pattern in which they cross at right angles. Figure 5 In the touch sensing electrode section 35, the touch sensor electrode 36 may be arranged closer to the visible side than the touch drive electrode 37. However, the touch drive electrode 37 may also be arranged closer to the visible side than the touch sensor electrode 36. In the touch sensing electrode section 35, the touch sensor electrode 36 and the touch drive electrode 37 may also be integrated.
[0208] exist Figure 5 In the embodiment, the touch sensing electrode portion 35 is disposed between the image forming layer 32 and the first transparent substrate 31 (closer to the visible side than the image forming layer 32). However, the touch sensing electrode portion 35 may also be disposed between the image forming layer 32 and the second transparent substrate 33 (closer to the lighting system side than the image forming layer 32).
[0209] In the touch sensing electrode portion 35 , the touch sensor electrodes 36 and the touch drive electrodes 37 may not be in contact with each other. For example, the touch sensor electrodes 36 may be arranged between the image forming layer 32 and the first transparent substrate 31 , and the touch drive electrodes 37 may be arranged between the image forming layer 32 and the second transparent substrate 33 .
[0210] The driving electrodes in the touch sensing electrode unit 35 (the touch driving electrodes 37 or electrodes in which the touch sensor electrodes 36 and the touch driving electrodes 37 are integrated) may also serve as common electrodes for controlling the image forming layer 32 .
[0211] The touch sensor electrode 36 (capacitive sensor), the touch drive electrode 37, or the electrode formed by integrating them, which constitutes the touch sensing electrode portion 35, functions as a transparent conductive layer. The material of the transparent conductive layer is not particularly limited, and examples thereof include metals such as gold, silver, copper, platinum, palladium, aluminum, nickel, chromium, titanium, iron, cobalt, tin, magnesium, tungsten, and alloys thereof. The material of the transparent conductive layer may also be an oxide of a metal such as indium, tin, zinc, gallium, antimony, zirconium, and cadmium. As the oxide, specifically, indium oxide, tin oxide, titanium oxide, cadmium oxide, and mixtures thereof may be mentioned. The material of the transparent conductive layer may also be a metal compound such as copper iodide. The material of the transparent conductive layer is preferably indium oxide (ITO) containing tin oxide, tin oxide containing antimony, and the like, and ITO is particularly preferred. When the material of the transparent conductive layer is ITO, the content of indium oxide in the transparent conductive layer is preferably 80 to 99% by weight, and the content of tin oxide is preferably 1 to 20% by weight.
[0212] The electrodes constituting the touch sensing electrode portion 35 (touch sensor electrodes 36, touch drive electrodes 37, or electrodes formed by integrating them) can be formed between the first transparent substrate 31 and the second transparent substrate 33 in the form of a transparent electrode pattern by conventional methods. The transparent electrode pattern is electrically connected to, for example, a lead formed at the end of the transparent substrate. The lead is connected to, for example, a controller IC. As the shape of the transparent electrode pattern, any shape corresponding to the purpose, such as a comb shape, a stripe shape, a diamond shape, etc., can be adopted. The thickness of the transparent electrode pattern is, for example, 10nm~100nm. The width of the transparent electrode pattern is, for example, 0.1mm~5mm.
[0213] [Embodiments of Image Display Device]
[0214] The image display device of this embodiment includes, for example, an image display panel 11A and a lighting system. Figure 4 and 5 The image display panel 11A is replaced by the image display panels 11B and 11C. In the image display device, the image display panel 11A is arranged, for example, closer to the visible side than the lighting system. The lighting system includes, for example, a backlight or a reflector, and irradiates light to the image display panel 11A.
[0215] The image display device may be an organic EL display or a liquid crystal display. However, the image display device is not limited to this example, and the image display device may be an electroluminescent (EL) display, a plasma display (PD), a field emission display (FED), etc. The image display device may be used for household appliances, in-vehicle use, public information display (PID) use, etc., and is preferably an in-vehicle display.
[0216] Example
[0217] Hereinafter, the present invention will be described in more detail by way of examples. However, the present invention is not limited to the examples shown below.
[0218] <Weight average molecular weight of (meth)acrylic polymer>
[0219] The weight average molecular weight (Mw) of the (meth)acrylic polymer was measured by GPC (gel permeation chromatography). Mw / Mn of the (meth)acrylic polymer was also measured in the same manner.
[0220] ·Analysis device: Made by Tosoh Corporation, HLC-8120GPC
[0221] ·Chromatographic column: G7000H manufactured by Tosoh Corporation XL +GMH XL +GMH XL
[0222] · Pillar size: 7.8mmφ×30cm each, total 90cm
[0223] Column temperature: 40℃
[0224] Flow rate: 0.8mL / min
[0225] Injection volume: 100μL
[0226] ·Eluent: Tetrahydrofuran
[0227] Detector: Differential Refractometer (RI)
[0228] Standard sample: polystyrene
[0229] [Preparation of (meth)acrylic polymer A1]
[0230] A monomer mixture containing 78.95 parts by weight of n-butyl acrylate (BA), 16 parts by weight of phenoxyethyl acrylate (PEA), 0.05 parts by weight of 4-hydroxybutyl acrylate (HBA), and 5 parts by weight of acrylic acid (AA) was added to a four-necked flask equipped with a stirring blade, a thermometer, a nitrogen inlet tube, and a condenser. Furthermore, 0.1 parts by weight of 2,2'-azobisisobutyronitrile (AIBN; manufactured by Kishida Chemical Co., Ltd.) as a polymerization initiator was added together with 100 parts by weight of ethyl acetate to 100 parts by weight of the monomer mixture. While slowly stirring the mixture, nitrogen was introduced into the flask to replace the nitrogen. The liquid temperature in the flask was maintained at about 55°C and a polymerization reaction was carried out for 8 hours, thereby preparing a solution of (meth)acrylic polymer A1 with a weight average molecular weight (Mw) of 2.5 million. The glass transition temperature of (meth)acrylic polymer A1 calculated according to the FOX formula is -43.5°C.
[0231] [Preparation of (meth)acrylic polymer A2]
[0232] The monomer mixture added to the flask was set to 60 parts by weight of 2-methoxyethyl acrylate (MEA), 39 parts by weight of BA, and 1 part by weight of HBA. In the same manner as in the preparation of the (meth)acrylic polymer A1, a solution of a (meth)acrylic polymer A2 having a weight average molecular weight (Mw) of 1.9 million was prepared. The glass transition temperature of the (meth)acrylic polymer A2 calculated by the FOX formula was -52.0°C.
[0233] [Preparation of (meth)acrylic polymer A3]
[0234] The monomer mixture added to the flask was set to 67 parts by weight of MEA, 22 parts by weight of BA, 10 parts by weight of PEA, and 1 part by weight of HBA. In the same manner as the preparation of the (meth)acrylic polymer A1, a solution of a (meth)acrylic polymer A3 having a weight average molecular weight (Mw) of 2,000,000 was prepared. The glass transition temperature of the (meth)acrylic polymer A3 calculated by the FOX formula was -45.0°C.
[0235] [Preparation of (meth)acrylic polymer A4]
[0236] A solution of (meth)acrylic polymer A4 having a weight average molecular weight (Mw) of 1.8 million was prepared in the same manner as (meth)acrylic polymer A1, except that the monomer mixture added to the flask was 99 parts by weight of BA and 1 part by weight of HBA. The glass transition temperature of (meth)acrylic polymer A4 calculated by the FOX formula was -55.0°C.
[0237] The monomers used for the synthesis of each (meth)acrylic polymer and the amount added are summarized in the following Table 1. The description of "-" in the table means that the component is not contained.
[0238]
[0239] (Example 1)
[0240] [TAC film with hard coating]
[0241] First, a resin solution (DIC, trade name: UNIDIC 17-806, solid content concentration: 80%) in which a UV-curable resin monomer or oligomer containing urethane acrylate as the main component is dissolved in butyl acetate is prepared. Relative to 100 parts by weight of the solid content of the resin solution, 5 parts by weight of a photopolymerization initiator (BASF, trade name: IRGACURE 907) and 0.1 parts by weight of a leveling agent (DIC, trade name: GRANDIC PC4100) are added to the resin solution. Next, cyclopentanone and propylene glycol monomethyl ether are added to the resin solution at a weight ratio of 45:55 so that the solid content concentration in the resin solution is adjusted to 36%. Thus, a hard coating forming material is prepared. The obtained forming material is applied to a transparent protective film (TAC film manufactured by Konica Minolta Co., Ltd., trade name "KC4UY") containing cellulose triacetate with a thickness of 40 μm to form a coating film. At this time, the thickness of the coating film was adjusted so that the thickness of the hard coating layer obtained by curing the forming material was adjusted to 7 μm. Next, the coating film was dried at 90° C. for 1 minute, and further irradiated with a high-pressure mercury lamp at a cumulative light intensity of 300 mJ / cm 2 Thus, the coating film is cured to obtain a TAC film with a hard coating layer (HC).
[0242] [Polarizing plate]
[0243] First, between multiple rollers with different speed ratios, a polyvinyl alcohol film with a thickness of 80 μm was dyed in an iodine solution with a concentration of 0.3% (temperature 30°C) for 1 minute and stretched to a stretch ratio of 3 times. Next, the obtained stretched film was immersed in an aqueous solution (temperature 60°C) with a concentration of 4% boric acid and a concentration of 10% potassium iodide for 0.5 minutes and stretched to a total stretch ratio of 6 times. Next, the stretched film was immersed in an aqueous solution (temperature 30°C) containing a concentration of 1.5% potassium iodide for 10 seconds, thereby washing it. Next, the stretched film was dried at 50°C for 4 minutes, thereby obtaining a polarizer with a thickness of 30 μm. A transparent protective film (thickness 30 μm) formed of a modified acrylic polymer having a lactone ring structure was bonded to one main surface of the obtained polarizer via a polyvinyl alcohol adhesive. The above-mentioned TAC film with a hard coating (thickness 47 μm) was bonded to the other main surface of the polarizer via a polyvinyl alcohol adhesive. At this time, the other main surface of the polarizer was bonded to the transparent protective film. The polarizer and the transparent protective film were bonded using a roll laminator. After the polarizer and the transparent protective film were bonded, the obtained laminate was dried in an oven at 70° C. for 5 minutes, thereby obtaining a polarizing plate composed of a hard coat layer and a polarizing film.
[0244] [Antistatic layer]
[0245] First, 50 parts of a solution containing PEDOT / PSS (manufactured by Nagase ChemteX, product number: N006-45-2A, N006-45-2B) and 50 parts of water were mixed to prepare a coating solution having a solid content concentration of 0.5% by weight. Next, the coating solution was applied to the surface of the polarizing film side of the polarizer. The obtained coating film was dried at 80°C for 2 minutes to prepare an antistatic layer. Thus, a laminate L1 consisting of a polarizer and an antistatic layer was obtained. The thickness of the antistatic layer was 60 nm.
[0246] [Adhesive sheet]
[0247] A solution of the (meth)acrylic adhesive composition of Example 1 was prepared by further mixing 0.3 parts by weight of a crosslinking agent (manufactured by Tosoh Corporation, product name: CORONATE 2770), 20 parts by weight of 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide salt (EMI-FSI) (manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd., product name: ELEXCEL AS110) as an antistatic agent, 0.5 parts by weight of an antioxidant (manufactured by BASF, product name: Irganox1010), and 0.4 parts by weight of a silane coupling agent (manufactured by KANEKA Corporation, product name: SILYL SAT010) with respect to 100 parts by weight of the solid content of the solution of the (meth)acrylic polymer A1.
[0248] Next, the obtained solution was applied to one side of a release liner (MRF38 manufactured by Mitsubishi Chemical Polyester Film Co., Ltd.). The release liner is a polyethylene terephthalate film treated with a silicone release agent. The obtained coating film was dried at 155° C. for 1 minute, thereby obtaining a laminate L2 having an adhesive sheet formed on the surface of the release liner. The thickness of the adhesive sheet was 20 μm.
[0249] [Optical laminate]
[0250] Next, the adhesive sheet of the laminate L2 obtained above was transferred to the antistatic layer of the laminate L1, thereby preparing a laminate L3 in which a polarizer, an antistatic layer, an adhesive sheet and a release liner were sequentially stacked. The release liner was peeled off from the laminate L3, thereby obtaining the optical laminate of Example 1.
[0251] (Example 2)
[0252] In the preparation of the pressure-sensitive adhesive sheet, a solution of the (meth)acrylic polymer A2 was used, and 6 parts by weight of EMI-FSI as an antistatic agent was used relative to 100 parts by weight of the solid content of the solution of the (meth)acrylic polymer A2. An optical laminate of Example 2 was obtained by the same method as Example 1.
[0253] (Example 3)
[0254] An optical layered body of Example 3 was obtained by the same method as in Example 2 except that the coating liquid of PEDOT / PSS was applied to the polarizing film so that the thickness of the antistatic layer would be 130 nm.
[0255] (Example 4)
[0256] The adhesive sheet and the antistatic layer were prepared by the following method, and the optical laminate of Example 4 was obtained by the same method as Example 1 except that the adhesive sheet and the antistatic layer were prepared by the following method. First, in the preparation of the adhesive sheet, a solution of (meth)acrylic polymer A3 was used. 8 parts by weight of EMI-FSI was used as an antistatic agent relative to 100 parts by weight of the solid content of the solution of (meth)acrylic polymer A3. The coating liquid of PEDOT / PSS was applied to the polarizing film in such a way that the thickness of the antistatic layer reached 30 nm.
[0257] (Example 5)
[0258] An optical laminate of Example 5 was obtained by the same method as in Example 4 except that the coating liquid of PEDOT / PSS was applied to the polarizing film so that the thickness of the antistatic layer would be 60 nm.
[0259] (Example 6)
[0260] An optical layered body of Example 6 was obtained by the same method as in Example 4 except that the coating liquid of PEDOT / PSS was applied to the polarizing film so that the thickness of the antistatic layer would be 130 nm.
[0261] (Example 7)
[0262] The laminate L1 consisting of a polarizer and an antistatic layer was prepared by the following method. In addition, the optical laminate of Example 7 was obtained by the same method as Example 4. First, 14 parts by weight of a solution containing CNT and a urethane adhesive (manufactured by Nagase ChemteX, product name: C-100A) and 86 parts by weight of water were mixed to obtain a coating solution with a solid content concentration of 0.5% by weight. Next, the coating solution was applied to the main surface of the polarizing film side of the above-mentioned polarizer. The obtained coating film was dried at 90°C for 1 minute to prepare an antistatic layer. Thus, a laminate L1 consisting of a polarizer and an antistatic layer was obtained. The thickness of the antistatic layer is 55nm.
[0263] (Example 8)
[0264] 15.1 parts by weight of a solution containing CNT and a urethane binder (product name: C-100A, manufactured by Nagase ChemteX Co., Ltd.) 0.7 parts by weight of an oxazoline-based adhesive (manufactured by Nippon Shokubai Co., Ltd., product name: EPOCROS (registered trademark) WS-700) and 84 parts by weight of water were mixed, and a coating liquid having a solid content concentration of 0.5% by weight was applied to the main surface of the polarizing film side of the above-mentioned polarizer. Otherwise, the optical laminate of Example 8 was obtained by the same method as Example 7.
[0265] (Example 10)
[0266] In the preparation of the adhesive sheet, 15 parts by weight of EMI-FSI as an antistatic agent was used relative to 100 parts by weight of the solid content of the solution of the (meth)acrylic polymer A2, and the coating liquid of PEDOT / PSS was applied to the polarizing film in such a way that the thickness of the antistatic layer reached 30 nm. Otherwise, the optical laminate of Example 10 was obtained by the same method as Example 2.
[0267] (Comparative Example 1)
[0268] The optical laminate of Comparative Example 1 was obtained by the same method as Example 1 except that the adhesive sheet was prepared by the following method and the antistatic layer was not prepared. In the preparation of the adhesive sheet, a solution of (meth)acrylic polymer A4 was used. 10 parts by weight of EMI-FSI as an antistatic agent was used relative to 100 parts by weight of the solid content of the solution of (meth)acrylic polymer A4.
[0269] The following evaluations were performed on Examples 1 to 10 and Comparative Example 1. Table 2 shows the evaluation results.
[0270] <Measurement of surface resistivity of adhesive sheet>
[0271] In each of the Examples and Comparative Examples, a laminate L2 having an adhesive sheet formed on the surface of a release liner was used, and the surface resistivity of the adhesive sheet was measured at 25° C. The surface resistivity of the adhesive sheet in the laminate L2 was measured using a resistivity meter (Hiresta MCP-HT800 manufactured by Mitsubishi Chemical Analytech) under the conditions of an applied voltage of 250 V and an applied time of 10 seconds.
[0272] <Measurement of surface resistivity of antistatic layer>
[0273] In each embodiment and comparative example, the surface resistivity of the antistatic layer was measured using the laminate L1 composed of a polarizer and an antistatic layer. The surface resistivity of the antistatic layer was measured at 25° C. using the resistivity meter described above and based on the method specified in JIS K6911:1995 under the conditions of applying a voltage of 10 V for 10 seconds.
[0274] <Measurement of Surface Resistivity of Pressure-Sensitive Adhesive Sheet Side in Optical Laminated Body>
[0275] The surface resistivity R1 of the adhesive sheet side of the optical laminate was measured at room temperature (25° C.) using the resistivity meter described above at an applied voltage of 250 V for 10 seconds.
[0276] For the determination of the surface resistivity R of the adhesive sheet side of the optical laminate at -15°C, the measurement was performed as described below before and after the weathering test. The polarizer side (hard coating side) of the laminate L3 was arranged on a cooling plate set at -15°C. After about 30 seconds, the release liner was immediately peeled off from the laminate L3 and the surface resistivity of the adhesive sheet side was measured. The above-mentioned resistivity meter was used to apply a voltage of 250V and an application time of 10 seconds to implement the surface resistivity R of the adhesive sheet side of the optical laminate at -15°C. The weathering test was implemented by the above-mentioned method using an ultraviolet fading tester (Suga Test Instruments Co., Ltd., U48HB).
[0277] Durability
[0278] The durability of the optical laminate was evaluated by the following method. The produced optical laminate was fixed to the surface of a glass plate (Corning, EAGLE XG) via its adhesive sheet to obtain an optical laminate with a glass plate. Fixing was implemented in an atmosphere of 24°C and 50% RH. Next, the optical laminate with a glass plate was treated in an autoclave at 50°C and 5 atmospheres (absolute pressure) for 15 minutes, and then placed until it was cooled to 24°C to stabilize the bonding between the optical laminate and the glass plate. Next, the optical laminate with a glass plate was left to stand in a heated atmosphere at 105°C for 500 hours. After standing, the atmosphere was restored to 24°C and 50% RH, and the peeling of the polarizer from the glass plate and the foaming between the glass plate and the polarizer were observed with the naked eye to evaluate the durability as described below.
[0279] (Evaluation Criteria)
[0280] A: No changes in appearance such as foaming and peeling were observed.
[0281] B: Although a small amount of individual peeling or foaming was observed at the edge, it was within the range of no problem in practical use.
[0282] C: A small amount of continuous peeling or foaming was observed at the edge, but it was within the range of no problem in practical use.
[0283] D: Remarkable peeling or foaming was observed at the edge, which was problematic in practical use.
[0284] <White evaluation>
[0285] Before and after the weather resistance test, the whitening of the optical laminate was evaluated by the following method. A glass plate simulating a transparent member on the front surface was bonded to the optical film side of the produced optical laminate via OCA (manufactured by Nitto Denko Corporation, LUCIACS CS9821; adhesive without acrylic monomer, thickness 200μm), and a laminate for evaluation simulating an image display device was produced. Next, the laminate for evaluation was bonded to the visible side of the embedded liquid crystal unit via its adhesive sheet, thereby producing an embedded liquid crystal unit with a laminate. Next, a polarizer was bonded to the opposite side of the embedded liquid crystal unit with the laminate in a manner that formed an orthogonal Nicol relationship, and a liquid crystal display panel was produced. After the liquid crystal display panel was cooled using a cooling plate set to -15°C, it was immediately placed on the backlight device, and the polarizer surface on the visible side was rubbed several times with nitrile gloves to generate static electricity. The time until the whitening part caused by static electricity disappeared was measured, and the evaluation was performed according to the following criteria. The weather resistance test was conducted by the above-mentioned method using an ultraviolet fading tester (U48HB manufactured by SugaTest Instruments Co., Ltd.) The evaluation result that was problematic in actual use was "D".
[0286] (Evaluation Criteria)
[0287] A: No whitening occurs.
[0288] B: Whitening occurred when rubbed several times, but disappeared within 1 second.
[0289] C: Whitening occurred when rubbed several times, but disappeared within more than 1 second and less than 5 seconds.
[0290] D: Whitening occurred after only one rubbing, and it took more than 5 seconds for it to disappear.
[0291]
[0292] As shown in Table 2, in the examples, the surface resistivity of the adhesive sheet side of the optical laminate at -15°C was 1.0×10 10 Ω / □ or less, and the durability is good. The optical laminate of the example is more suitable for suppressing display failure in a low temperature environment, typically whitening due to charging.
[0293] Industrial Applicability
[0294] The optical layered body of the present invention is particularly suitable for an image display device used in an environment such as the interior of a vehicle where other electronic devices are present around and static electricity is easily generated and the environment is easily affected by the outside temperature and reaches a low temperature.
Claims
1. An optical laminate comprising: Adhesive sheet, Antistatic layer, and Optical film, The adhesive sheet is formed from an adhesive composition comprising a polymer (A) and an antistatic agent, The surface resistivity of the adhesive sheet side of the optical laminate at -15°C was 1.0×10 10 Ω / □ or less.
2. The optical layered body according to claim 1, wherein: The surface resistivity of the antistatic layer at 25°C is 3.0×10 8 Ω / □ or less.
3. The optical laminate according to claim 2, wherein: The surface resistivity of the antistatic layer at 25°C is 1.0×10 7 Ω / □ or more and less than 1.0×10 8 Ω / □.
4. The optical laminate according to claim 1, wherein: The polymer (A) is a (meth)acrylic polymer.
5. The optical layered body according to claim 1, wherein: The polymer (A) has a polyether structure.
6. The optical layered body according to claim 1, wherein: The polymer (A) has a structural unit derived from a monomer represented by the following formula (1), , In the formula (1), R 1 is a hydrogen atom or a methyl group, R 2 It is an alkyl group which can be a linear alkyl group or an alkyl group having a branch, and n is an integer of 1 to 15.
7. The optical layered body according to claim 5, wherein: The polymer (A) has a structural unit derived from an aromatic ring-containing monomer.
8. The optical layered body according to claim 1, wherein: In the pressure-sensitive adhesive composition, the amount of the antistatic agent blended is less than 10 parts by weight based on 100 parts by weight of the polymer (A).
9. The optical layered body according to claim 1, wherein: The glass transition temperature of the polymer (A) calculated by the FOX equation is -40°C or lower.
10. The optical layered body according to claim 9, wherein: The glass transition temperature is -45°C or lower. 11 . An image display panel comprising the optical layered body according to claim 1 . 12 . An image display device comprising the image display panel according to claim 11 .
Citation Information
Patent Citations
Antistatic agent composition
CN101089112A
Optical laminate, polarizing plate, and display apparatus using the same
CN102012532A
Fiber having characteristics of static resistance, acid-alkali resistance, heat insulation and flame resistance
CN103451757A
Core shell particle toughened polyethylene antistatic master batch and preparation method thereof
CN104419052A
Adhesive composition and protective film using same
CN114525102A